Association of Biochemical Parameters in Chronic Drug Addict Patients; A Case-Control Study - Muhammad Asif Zeb, Syed Izaz Shah, Pervez Muhammad, Insafia Mehmood, Sajid Khan, Sana Kanwal Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the effect of a biochemical parameter in chronic drug addict patients in Peshawar, Khyber Pukhtunkhwa. Materials and Methods: Blood samples of 90 drug addicts were randomly collected, 45 were hashish and 45 were heroin addicts. Drug addicts having hepatitis B and C infections were excluded from the study. Three milliliters of blood samples were collected in the lithium heparin tube using an aseptic technique for the determination of Alanine transaminase, Aspartate transaminase, Triglycerides, and Cholesterol. Results: Cholesterol was significantly decreased (P=0.00) in the age group between 21 and 40 years followed by the age group less than 20 years (P=0.02). Liver enzymes were significantly elevated but, were more significant up to 40 years (P=0.00). Conclusion: Heroin and hashish affect liver function enzymes Alanine transaminase and aspartate transaminase and cause a reduction in cholesterol levels in individuals using drugs for a long period. Keywords: Alanine transaminase (ALT), Aspartate transaminase (AST), Triglycerides, and Cholesterol.